The Southern World as a Destination of International Students: an Analysis of 50 Tertiary Education Institutions in Vietnam - Pham, Hiep Hung (Journal of Contemporary Eastern Asia, 2022)
Traditionally, students from the Southern world tend to cross their national borders to study abroad. However, in recent times, we have observed a trend in which more and more students, both full-time and short-term, select Southern countries as destinations for overseas education. This paper contributes to the sparse literature on the above phenomenon, examining the case of Vietnam. We surveyed 50 universities and colleges about their international student profiles (including statistics and nationalities) and their strategies for attracting international students. The findings of this study provide implications for Vietnam's policymakers and university/college leaders and other Southern countries when implementing the internationalization of tertiary education.